2005
DOI: 10.1093/jjco/hyi123
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Esophageal Stricture Due to Metastatic Breast Cancer Diagnosed by Endoscopic Mucosal Resection

Abstract: Metastasis of breast cancer to the esophagus has been reported but is rare. It is often difficult to diagnose metastases of breast cancer to the esophagus because they are often located in the submucosa and covered with normal mucosa. Although several methods have been reported in order to obtain specimens for pathological diagnosis, the adverse effects including bleeding and perforation were considerable problems. We report a case of a patient with esophageal stricture due to metastatic breast cancer to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…Asch et al also reported an autopsy series of 337 patients with diagnosis of breast cancer and only 20 cases of esophageal metastases, of which none had specific gastrointestinal symptoms on their previous medical history. [5] On this group of patients, dysphagia is the most common symptom and has been reported to appear within eight years of the primary diagnosis of breast carcinoma, [5] as presented on the patient exposed in this case report. There are many practices accepted regarding treatment for these patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Asch et al also reported an autopsy series of 337 patients with diagnosis of breast cancer and only 20 cases of esophageal metastases, of which none had specific gastrointestinal symptoms on their previous medical history. [5] On this group of patients, dysphagia is the most common symptom and has been reported to appear within eight years of the primary diagnosis of breast carcinoma, [5] as presented on the patient exposed in this case report. There are many practices accepted regarding treatment for these patients.…”
Section: Discussionmentioning
confidence: 85%
“…There are many practices accepted regarding treatment for these patients. Studies had reported that endoscopic resection technique is a suitable option with adequate results and is considered a safe method, [5] however, is difficult to identify this pathology before it manifests with a complication like stenosis or perforation. In the scenario of complication, like the case presented in this paper, the minimally invasive approach with laparoscopic surgery provides a good option for a better postoperative recovery and a prompt referral to an Oncology service to continue treatment providing a better chance to a good survival in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 23 cases, in 11 cases, including our case [8, 13-17, 19, 20], the esophagus was the first recurrent site, and in 7 cases [7,[9][10][11][12][13], it was not the first site of recurrence. In the other five cases [1,18], this detail is not mentioned. A long interval between primary treatment for the breast tumor and its recurrence with esophageal involvement has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…From the standpoint of metastatic esophageal tumors, the most common malignancy to metastasize to the esophagus is breast carcinoma [3,6,7]. To the best of our knowledge, there have been 23 cases (16 case reports) including our case of esophageal metastasis from breast cancer in the English-language medical literature for the last 20 years [1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Among 23 cases, in 11 cases, including our case [8, 13-17, 19, 20], the esophagus was the first recurrent site, and in 7 cases [7,[9][10][11][12][13], it was not the first site of recurrence.…”
Section: Discussionmentioning
confidence: 99%